Clinical implications and cost-effectiveness analysis of rivaroxaban in patients with coronary artery disease or peripheral arterial disease in the Netherlands. (1st January 2021) - Spoorendonk, J. A.; Briere, J.-B.; Bowrin, K.; Millier, A.; Coppens, M.; Tempelaar, S.; Verheggen, B.
Abstract: Background: Patients with stable coronary artery disease (CAD) or peripheral artery disease (PAD) are at substantial risk of atherothrombotic events. The COMPASS trial showed that patients with stable CAD or PAD experienced significant benefits after treatment with rivaroxaban in combination with acetylsalicylic acid (ASA) compared with ASA alone. This paper aims to provide insight into the clinical and economic consequences of treatment with rivaroxaban from a Dutch societal perspective. Methods: The clinical and economic implications of rivaroxaban in terms of the number of events prevented, costs, the incremental cost per life-years gained (LYG), and incremental cost per quality-adjusted life-years (QALYs) were determined based on a cost-effectiveness model for patients with stable CAD or PAD and in high-risk subgroups (i.e. patients with CAD and PAD, CAD and prior myocardial infarction and renal impairment, CAD and heart failure) using results from the Cardiovascular OutcoMes for People Using Anticoagulation Strategies (COMPASS) trial. Results: Patients treated with rivaroxaban have an expected increased discounted life expectancy of 0.67 years. In high-risk groups discounted incremental life expectancy ranged from 1.33 to 1.90 years. The incremental cost-effectiveness ratio for the full COMPASS population was €9, 760/LYG and €12, 033/QALY, whereas, for high-risk subgroups of patients with underlying conditions, incremental cost-effectiveness ratios ranged from €2, 966/LYG to €5, 052/LYG and from €3, 940/QALY to €6, 815/QALY. Results from the sensitivity analyses revealed that the model results were robust to variations in single or multiple input parameters at once. Conclusions: The cost-effectiveness analysis showed that rivaroxaban in combination with ASA is a cost-effective treatment option in stable CAD or PAD patients. Rivaroxaban in combination with ASA is even more cost-effective in high-risk subgroups.